Tinjauan Hukum Islam terhadap Pelaksanaan Pidana Kurungan bagi Anak Nakal di Rutan Anak Blitar - A. Imam Baihaqi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2020)
Among the criminal problem that are faced by society today is children crimes and violations, which legally referred to as "child crime". Consequently, they must be held accountable through a judicial process that can lead to imprisonment. In Indonesia, one of the places for child incarceration is in the Children's Correction Center (LPA) of Blitar. The study aims to determine the implementation of imprisonment policy for children in LPA Blitar and the Islamic criminal law's perspective. The results of this study concluded that the criminal justice process for children criminals in LPA Blitar prevails under the current law. As for the efforts of the Blitar LPA in its implementation of the policy is to provide guidance and education in a best and fair manner tailored with the evolution of children's psychology. In Islamic law, there is no prohibition about children's punishment as long as the child has passed the age of baligh, but must prioritize the education and mental development of the child. It is in line with sharia law and relevant law in Indonesia